(untitled) (Applied Biological Research, 2011)
Studies on the preparation of ber chuhara through osmo-air drying process were conducted at the Division of Post Harvest Technology, SKUAST-J, Jammu. Before making chuhara, the ber (Zizyphus mauritiana Lamk.) fruits were subjected to different pre-treatments, viz., lye peeling (5% NaOH for 5 min.), citric acid treatment (5% for 5 min.) and KMS treatment (@ 4000 ppm for 12 h). Pretreated ber were dipped different sugar concentrations of 40, 50, 60 and 70° Brix at 24, 48 and 72 h. The treated fruits were then dried at 522°C for 6 h in a dehydrator till a chewable and appealing product was developed. Sensory evaluation revealed that 70°Brix at 72 h gave best chuhara-like product from ber through osmo-air drying process and could be an acceptable product.